Implementasi Aplikasi Buku Kas Untuk Menunjang Kompetensi Siswa Jurusan Akuntansi - Ni Luh Wiwik Sri Rahayu Ginantra; Christina Purnama Yanti; Theresia Hendrawati (LPPM POLITEKNIK LP3I, 2024)
At this time, people are more directed towards consumptive behavior in living their daily lives. The same is true for teenagers, the majority of whom follow a lifestyle in accordance with current trends. By following this trend, it is certain that adolescents will spend more money and not commensurate with existing income. Similarly, students at SMK Dwijendra Denpasar majoring in Accounting have problems where students are difficult to manage their personal finances. With our community service activities, it is hoped that it can help students in terms of a good financial management system and can improve skills and knowledge about how to manage personal finances so that later in the world of work it is expected to be able to manage company finances. The output of this research is that students are able to identify and prioritize the main priorities for allocating their personal funds. In addition, students can feel financial security in meeting sudden needs, because they have sufficient savings in the future.